Large size symptomatic uterine leiomyoma. Is saving the uterus feasible? - Татарчук, Т. Ф; Косей, Н. В.; Васильченко, Л. А.; Джупін, В. А. (REPRODUCTIVE ENDOCRINOLOGY, 2015)
The paper presents the clinical case of large size uterine leiomyoma complicated by uterine bleeding and venous thrombosis of iliofemoral segment. Due to the use of minimally invasive methods successful staged organ saving treatment of leiomyoma with coexisting somatic pathology was performed after which the patient has a good perspective of fertility preservation.